The effect of coal ratio on the high-lead slag reduction process - Zhang Z.; Li W.; Zhan J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The effect of coal ratio on the high-lead slag reduction was reported in this article. First, the phase diagrams of the PbOFeO- SiO2-2%CaO-10%ZnO slag system at various temperatures and coal ratios were thermodynamically constructed. Next, the density, the melting temperature, the viscosity, the chemical composition and the phase transformation of the reduced slag were investigated. The thermodynamic results indicated that the variation of coal ratio could affect the chemical composition of the reduced slag, which led the physical properties of the reduced slag to change further. The experimental results illustrated that the content of lead and copper in the reduced slag decreased, while the contents of iron, silicon, calcium and zinc in the reduced slag increased as the coal ratio increased, which led the density and viscosity of the reduced slag to decrease further. The melting temperature of the reduced slag increased sharply when the coal ratio varied in the range of 1.5% to 3%. The mineralogy of the reduced slag indicated that lead mainly existed in the reduced slag in the form of metallic lead, while the iron and zinc were mainly enriched in the reduced slag in the form of a silicate phase. The industrial verification test results demonstrated that the average recovery rate of the lead exceeded 96.0%, the average lead content in the reduced slag was below 2.0% and the average fume rate was approximately 12.0%.